Development of pilot black soldier fly (BSF) facility for sustainable food waste management - Muhamad Yusoff, Yusrina Afifa (2023)
The outrageous food waste disposal has contributed to environmental pollution and land scarcity. To maintain a sustainable environment and encourage a circular economy, the alternate action of food waste bioconversion by using black soldier fly (BSF), Hermetia illucens larvae (BSFL) has been introduced to promote environmentally sustainable food waste management. A pilot facility was developed to harvest BSFL that can be utilized in treating the food waste from UiTM Puncak Alam Campus. This facility was established to investigate the feasibility of a smallscale cultivation system of BSFL and its potential in food waste valorization. Firstly, the optimum rearing condition (temperature, humidity and light intensity) of BSFL was determined based on the daily BSF egg production. As for food waste composting that particularly utilized organic waste, the yield of the compost and its biomass were also determined. It was found that the pilot facility can sustainably support the colonization cycle of BSF. A weekly introduction of one kg of prepupae into a 0.6 x 0.6 x 1.5 m cage resulted in 22.1 ± 1.5 g of BSF eggs per day. The pilot facility is therefore expected to be able to process up to 300 kg of food waste every day with the assumption that 2.25 kg larvae or one g of BSF eggs can be utilized to degrade 15 kg of food waste. In addition, the study also assessed that one kg of food waste could produce 0.3 ± 0.05 kg of compost and 0.15 ± 0.02 kg of larvae. Therefore, it could be concluded that the pilot facility has the potential to cultivate and utilize BSFL for food waste valorization.